HUBUNGAN ANTARA KEMAMPUAN MEMORI DAN MOTIVASI BELAJAR BIOLOGI DENGAN HASIL BELAJARBIOLOGI RANAH KOGNITIF SISWA SMA NEGERI 2 MADIUN TAHUN PELAJARAN 2011/2012 - Habsari, Afrisa Mustika; Karyanto, Puguh; Probosari, Riezky Maya (Pendidikan Biologi, 2012)
ABSTRACT ? The  aims of the research were  to find out  the correlation  between: 1) memory ability with cognitive learning achievement of biology of student of SMA Negeri 2 Madiun in academic year of 2011/2012, 2) learning motivation of biology with cognitive learning achievement  of biology  of student  of SMA Negeri  2 Madiun in academic year of 2011/2012,3) memory ability and learning motivation of biology with  cognitive learning achievement  of student  of SMA Negeri  2 Madiun in academic year of 2011/2012. This  is  a correlational research.  The population  taken  were all of the students of SMA Negeri  2 Madiun  in academic year of 2011/2012. The sample was taken among  676  samples of student using  stratified  random sampling technique.  Documentation technique was used to uncover student?s  cognitive learning achievement  and memory ability was measured by using testtechnique. While learning motivation of biology was measured by using questionnaire technique.  The obtained data was analysed using linier regression analysis in SPSS 16. The results  showed that (1)  there was a  positive  correlation between memory ability with cognitive learning achievement of biology ofstudentof SMA Negeri  2 Madiun  in academic year of 2011/2012, 2)  there was a  positive correlation between  learning motivation of biology  with  cognitive learning achievement  of biology ofstudentof SMA Negeri  2 Madiun  in academic year of 2011/2012,  3)  there was a  positive  correlation between  memory ability  and learning motivation of biology with  cognitive learning achievement  of biology of student of SMA Negeri  2 Madiun  in academic year of 2011/2012.  Each of independent  variable, that is  memory ability  and  learning motivation of biology has contribution to dependent variable, that is  cognitive  learning achievement of biology. Keywords :Memory ability,  learning motivation,cognitive learning achievement in biology, linier regression analysis